Experimental study on the longitudinal resistance of WJ-8 fasteners subjected to torque and vertical loading in continuously welded rails. (November 2020) - Zeng, Zhiping; Tian, Chunyu; Tu, Qinming; Shuaibu, Abdulmumin Ahmed; Wang, Weidong
The key functions of the fastener system are to hold the rail against the sleepers and to restrain the rail from all forms of movements that could lead to loss of geometry and stability of the track. Thus, fastener resistance is an important parameter in the continuously welded rail technology. This study investigates the characteristics of the longitudinal resistance of WJ-8 fasteners subjected to varying torques and vertical loadings. The vertical loading was applied to the rail section through a reaction frame, while the torque was applied using a digital torque wrench. Two types of fasteners, conventional-resistance and small-resistance fasteners, were tested in this study. The study shows that: (1) The growth rate of the longitudinal resistance of the fastener is independent of the vertical loading until the fastener slips. (2) The slip resistance of fasteners increases as the torque and vertical loading are increased. (3) The relationship between the longitudinal resistance and the displacement of fasteners at varying torques and vertical loadings fits a power index function. (4) The relationship between the longitudinal resistance and the displacement of the fastener exhibits hysteresis. The study serves as a reference for verifying and improving future calculation methods for the longitudinal resistance of fasteners in continuously welded rails.